Effects Drying on The Indonesian Citrus Peel Antioxidant Activity - Nindya Atika Indrastuti; Siti Aminah; Syifa Fauziah; Dwi Handayani (Indonesian Journal of Applied Research (IJAR), 2020)
The high production and market demand of citrus fruits for household and industrial consumption make it peels one of the most abundant wastes found in the environment. On the other hand, citrus peel is well known for bioactive compounds that beneficial to human health, including phenolic, flavonoids, and antioxidants. Recently, citrus peel waste is starting to be used for food ingredients. The drying technique is one of the solutions that can be used for preserving citrus peel waste which has high water content. This study was objected to identifying the effect of the drying type (tray dryer and freeze dryer) on the antioxidant activity alteration of three citrus varieties that commonly cultivated in Indonesia, i.e. pummelo/jeruk Bali (C. maxima Herr.), mandarine citrus/jeruk keprok (Citrus reticulate) and sweet orange/tangerine/jeruk Medan (C. microcarpa L. and C. sinensis L.). The antioxidant activity was measured by calculating the IC50 value. The results showed ethanol extract of fresh mandarin citrus peels showed the lowest IC50 (14.46 ± 3.63 mg/mL) compared to fresh pummelo peels (26.48 ± 5.17 mg/mL) and fresh tangerine peels (16.94 ± 1.51 mg/mL). Tray dryer technique reduced the IC50 value of the peel extracts of pummelo, mandarine citrus and tangerine were 78.92%, 72.34%, and 79.69%, respectively. Whereas Freeze dryer drying reduced the IC50 value of pummelo, mandarine citrus and tangerine peel extracts were 59.21%, 69.43%, and 80.46%, respectively.